An Analysis of the Relationship between Digital Game Playing Motivation and Digital Game Addiction among Children - HAZAR, Zekihan (Asian Journal of Education and Training, 2019)
The aim of this study is to investigate the relationship between digital game addiction and the motivation for digital game-playing, and to develop suggestions towards the solution of the research problem through the relationship between these two concepts. The study is designed according to the quantitative research method and the relational screening model was administered. In the study, a Personal Information Form, Digital Game Addiction Scale for Children, and the Digital Game-Playing Motivation Scale were used. The data obtained were analyzed with the SPSS 24 package program, and descriptive statistics, t-Test and OneWay Anova, Pearson correlation and regression analyses were run on the data. According to search results, a positive and significant correlation was seen between the participants’ digital game playing motivation and digital game addiction. In addition, higher levels of digital game playing motivation and digital game addiction among the participants whose parents play digital games; lower levels of digital game playing motivation and digital game addiction among the participants who hold athlete’s license and the finding that digital game playing motivation and digital game addiction increase in parallel with age are important results of this study.